Theological Divergence and Political Convergence in Salafiyyah and the Muslim Brotherhood - Hotimah, Husnul; Salsabila, Salsabila (An-Nur International Journal of Islamic Thought, 2025)
This study explores the theological and political dimensions of two major Islamic revivalist movements: Salafiyyah and the Muslim Brotherhood. It begins by situating both within the broader context of colonialism, the collapse of the Ottoman Caliphate, and the subsequent crisis of modernity in the Muslim world. Methodologically grounded in library-based qualitative research and comparative textual analysis, the study traces the evolution of Salafiyyah from Hadith-centered traditionalism to its revivalist expression in figures such as Ahmad ibn Hanbal, Ibn Taymiyyah, and Muhammad ibn 'Abd al-Wahhab. Parallelly, it examines the emergence of the Muslim Brotherhood under Hasan al-Banna, focusing on its holistic Islamic vision that integrates theology with education, political activism, and social welfare. Results indicate that while both movements uphold core Sunni beliefs—particularly Tawḥīd and the rejection of Bidʿah—they differ sharply in strategic orientation. Salafiyyah emphasizes theological rigidity and purification, often leading to polemical exclusivism, whereas the Brotherhood employs theology as a platform for unity and pragmatic reform. These contrasting approaches reflect deeper tensions in how modern Muslims negotiate tradition, authority, and modernity. The study concludes by highlighting the contribution of both movements to Islamic revivalism and their enduring impact on contemporary Muslim political and spiritual thought.